Late glacial and deglacial paleoceanographic and environmental changes at Vestnesa Ridge, Fram Strait: challenges in reading methane-influenced sedimentary records - Sztybor, Kamila (UiT Norges arktiske universitet, 2017)
Denne avhandlingen er basert på fire sedimentkjerner fra et område ved Vest Svalbard hvor metan siver opp fra havbunnen. Studien fokuserer på å rekonstruere graden av metanutsiving i fortiden, samt klimavariasjoner i Arktiske strøk med bruk av bentiske foraminiferer. Foraminiferer er encellede organismer som produserer en kalkholdig skall som bevares i sedimentene på havbunnen. Ved å se på geokjemiske sammensetningen av disse fossilerte skallene, er det mulig å rekonstruere både paleoseanografiske forhold og episoder av økt metan-flux i havbunnen. Basert på isotopisk analyse av de fossilerte skallene og den assosierte karbonatholdige skorpen har vi identifisert massivt metanutslipp i løpet av issmeltingsperioden for 15.000-13.000 år siden. Rekonstruksjoner av paleo-utsiving av metan er viktig å estimere bidraget av metan til hav-atmosfæresystemet, spesielt sett i lys av den pågående globale oppvarmingen og økende dyphavstemperaturene som er forsterket i Arktis. This thesis is based on four sediment cores from the western Svalbard margin from an area where methane is released from the seafloor. The study focuses on reconstructing methane seepage events in the past and climate variability in this high Arctic region with a use of benthic foraminifera. Foraminifera are single celled organisms that produce a calcareous shell that is preserved in seafloor sediments. By reading the geochemical records of the fossil shells, we can reconstruct both paleoceanographic conditions and episodes of enhanced methane flux towards the seafloor. Based on the isotopic record of the fossilized shells and associated carbonate crust we have identified massive methane release during the deglaciation 15,000-13,000 years ago. Reconstructions of paleo-seepage are important to estimate the contribution of methane to the ocean-atmosphere system, especially in the light of ongoing global warming and increasing deep-sea temperatures that are amplified in the Arctic region.